1995
DOI: 10.1021/ja00152a010
|View full text |Cite
|
Sign up to set email alerts
|

Thermally-Induced 1,2-Shifts To Convert Olefins to Carbenes: Does Silicon Do It? If So, Why Not Carbon?

Abstract: Thermal isomerization of olefins to carbenes via a 1,2-silyl shift was examined by both experiment and theory. No evidence of this rearrangement was found for acyclic vinylsilanes, nor could electronic assistance by silicon be identified in cis, trans isomerizations. Serendipitous synthesis of a 2,4-dimethylene-1,3-disilacyclobutane allowed a kinetic examination of its gas-phase, thermal ring expansion to a 2-methylene-1,3-disilacyclopentene. The Arrhenius parameters (log A = 12.48, Eact = 54.09 kcallmol) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Bearing in mind that cyclopropylidenes such as 5 , when generated from a diazocyclopropane7 or a 1,1‐dihalocyclopropane via a carbenoid,8 are prone to undergo ring opening to allenes, we conceived the possibility that in a 1‐silyl‐substituted cyclopropene 2 , a fast 1,2‐silyl shift9,10 might occur in the first step leading to a cyclopropylidene 5 ,11 which could then rearrange to the observed allene 8 . An example of a 1,2‐silyl shift leading to a carbene has been reported by Barton et al,12 who found that heating of 1,1,3,3‐tetramethyl‐2,4‐dimethylene‐1,3‐disilacyclobutane results in its rearrangement by consecutive 1,2‐silyl and 1,2‐H shifts via 1,1,3,3‐tetramethyl‐2‐methylene‐1,3‐disilacyclopent‐4‐ylidene to 1,1,3,3‐tetramethyl‐2‐methylene‐1,3‐disilacyclopent‐4‐ene. Of course, an allene 8 would also result from a fast 1,2‐silyl shift in the vinylcarbene 4 .…”
Section: Introductionmentioning
confidence: 83%
“…Bearing in mind that cyclopropylidenes such as 5 , when generated from a diazocyclopropane7 or a 1,1‐dihalocyclopropane via a carbenoid,8 are prone to undergo ring opening to allenes, we conceived the possibility that in a 1‐silyl‐substituted cyclopropene 2 , a fast 1,2‐silyl shift9,10 might occur in the first step leading to a cyclopropylidene 5 ,11 which could then rearrange to the observed allene 8 . An example of a 1,2‐silyl shift leading to a carbene has been reported by Barton et al,12 who found that heating of 1,1,3,3‐tetramethyl‐2,4‐dimethylene‐1,3‐disilacyclobutane results in its rearrangement by consecutive 1,2‐silyl and 1,2‐H shifts via 1,1,3,3‐tetramethyl‐2‐methylene‐1,3‐disilacyclopent‐4‐ylidene to 1,1,3,3‐tetramethyl‐2‐methylene‐1,3‐disilacyclopent‐4‐ene. Of course, an allene 8 would also result from a fast 1,2‐silyl shift in the vinylcarbene 4 .…”
Section: Introductionmentioning
confidence: 83%
“…In case of free carbenes the 1,2-shift of the b-substituent to the carbene centre is usually a rapid process [13]. The ease of this rearrangement increases for b-substituents forming weak bonds to carbon, such as silicon [14,15]. The same must be true for transition metal groups, Re(CO) 5 and Fe(CO) 2 Cp.…”
Section: The Mechanism Of Chloride Substitution In Cf 2 @Cfcl (I) By mentioning
confidence: 99%
“…As for the b-element substituted carbenes we can find some data only for silicon. It was shown (at MP2 or B3LYP levels of theory) that bsilicon substituted carbenes represent no minima on potential energy surface rearranging to the corresponding alkenes without an activation barrier [14,15].…”
Section: Dft Study Of Carbenes [Mcf 2 Cf:] and Carbenoids [Mcf 2 Cfclmentioning
confidence: 99%
“…15–17 In the 13 C NMR spectroscopic data of 9 , the H‐substituted carbon atom C(sp 2 )‐3 has a slightly smaller 1 J PC constant ( 1 J PC = 53.7 Hz, C H) than the C‐5 ( 1 J PC = 59.7 Hz, C Mes*), which might represent a 5‐substituted 1 H ‐1,2,4‐diazaphosphole 18–20. The exclusive formation of 9 without a 1,2,3‐diazaphosphole isomer indicates that regioselective [2+3] cycloaddition of 1 with the CN 2 moiety proceeds under kinetic control by the bulky Mes* group21 followed by subsequent silyl group migration13,14,16 to gain higher aromatic stabilization. The N–Si bond in 9 is sensitive to alcohol and moisture, and desilylation took place to afford 10 by addition of ethanol (Scheme ) 13,22.…”
Section: Resultsmentioning
confidence: 99%